Environmental study to estimate the pollution of some heavy elements in the content of leaves and fruits of the olive plant in the city of Mosul - Yahya Al-Mashadani; Afaf Abdullah (College of Education for Pure Sciences, 2007)
This practical study was conducted in Mosul city. A one hundred sites were chosen from quarters, industrialand commercial regions, main and secondary streets. This study included the pollution of leaves and the fruit of olive by the mineral elements (lead, zinc and cadmium) to check the range of the concentration of these elements. This study extended since October. 1999 to October/ 2000 . The results of the practical study appointed to a fact that the concentrations and the elements of mineral elements in leaves and fruits were different and heterogeneous among the regions and the season; while the highest concentrations were in the regions which included the city centre and the industrial regions. This pollution belongs to the overpopulation in the region which depends on kerosene as a fuel in the domestic uses as well as the crowded movement of traffic with what cars exhaust such smoke and gases as a result to the consabustion. The high concentrations appeared in winter, while the low onces appeared for and modern quarters of the city centre and the industrial regions besides the region of the comparison. However, the concentrations of the elements in the leaves and the fruits where higher than the previous studies in the city as compared with some Arabic and international studies. There were a heterogeneous in the concentrations of the mineral elements among the general and subsidiary streets for dwelling quarters.